Therapists' experience of the cognitive orientation to daily occupational performance (CO-OP) approach: Shifting from conventional practice. (17th February 2020) - Chui, Adora; Mazzitti, Daniela; Nalder, Emily; Cameron, Debra; Polatajko, Helene J.; Dawson, Deirdre R.
Abstract: Background: The CO-OP Approach TM has been increasingly used in research and practice, yet its critical elements and implementation challenges are largely undescribed. Obtaining therapists' perspectives on CO-OP may reveal insights into potential critical and mediating factors. Aim/Objective : To explore the experiences of CO-OP therapists by understanding their perceptions on the approach compared with conventional practice, and by identifying mediating factors in its implementation. Material and Method : This exploratory study utilized a qualitative descriptive design. A purposive sample of occupational therapists (n = 3) was interviewed. Data were analyzed using thematic analysis and themes were validated within a focus group. Results/Findings : Three themes were identified: 'CO-OP works, ' 'CO-OP delivery is mediated by contextual factors, ' and 'CO-OP shifts the therapeutic approach.' Therapists perceived CO-OP to be efficacious for client-centred goal attainment. Guided discovery and the problem-solving strategy were identified as unique and challenging CO-OP elements. Mediating factors such as level of cognitive impairment and quality of family member involvement may affect CO-OP efficacy. Conclusions : Therapists found CO-OP to be efficacious and adopted unique elements into their professional approaches. Significance: This is the first study to investigate CO-OP therapists' experiences. Future research is recommended to enhance training of therapists in key CO-OP features.